MONTAGEM E RESOLUÇÃO DE PROBLEMA DE OTIMIZAÇÃO NÃO LINEAR RESTRITO PARA PREDIZER A COMPOSIÇÃO DOS GASES DE COMBUSTÃO EM CALDEIRA SIDERÚRGICA - Fabri Turetta, Leticia; Ferreira Da Costa Junior, Esly; Oliveira Souza Da Costa, Andréa (LINKSCIENCEPLACE, 2026)
The development of the steel industry has increased energy demand, exerting a strong influence in the use of energy resources. The energy use is very important because it permits the steelmaking reduced considerably its costs associated with the energy matrix. In the steelmaking process the stages of coke, steelworks and blast furnace produce three gases with high capacity for energy generation. The three gases produced are directed thermoelectric plants. The thermoelectric plant is an industrial plant that transforms the thermal energy obtained from the burning of fuels in boilers in electricity. The burning of this fuel mix generates beyond energy, exhaust gases. With the minimization of Gibbs free energy can predict the output composition of the steel gas at the boiler, equipment at the thermoelectric central. The optimization problem has been mounted thus defining the objective function and restrictions to be solved in Matlab program. It was possible to predict the output composition of the exhaust gases of a boiler with varying the feed air to the system.